Effectiveness of an educational video on the knowledge of lay people in the waiting room about cardiopulmonary resuscitation. - de Araújo, Dariane Veríssimo (2021)
Aim: To evaluate the effectiveness of an educational video about cardiopulmonary resuscitation on lay people in the waiting room of a basic health unit. Methods: This was a quasi-experimental study of the before-and-after type conducted from May to November 2019. The sample consisted of 66 people who were in the waiting room waiting for consultation in the Basic Health Unit. To evaluate the knowledge, a theoretical test was used before and after the educational intervention mediated by the educational video "Cardiorespiratory arrest: how to act to save". Descriptive statistics and the McNemar and Wilcoxon tests were used in the analysis. Results: In the pre-test, there was a median of correct answers of 5 (interquartile range = 7), while in the post-test, the median was 8 (interquartile range = 7), p<0.001. There was an increase in knowledge, especially on the questions about CRA recognition (p<0.001), Emergency mobile care service (SAMU) number (p<0.001), victim position (p<0.001), and compression force level (p<0.001). Conclusion: The educational video is effective in improving laypersons' knowledge about cardiopulmonary resuscitation and can be used in the health education of patients in the waiting room.